2016
DOI: 10.1016/j.meteno.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of respiration and oxidative stress response on recombinant α-amylase production by Saccharomyces cerevisiae

Abstract: Studying protein production is important for fundamental research on cell biology and applied research for biotechnology. Yeast Saccharomyces cerevisiae is an attractive workhorse for production of recombinant proteins as it does not secrete many endogenous proteins and it is therefore easy to purify a secreted product. However, recombinant production at high rates represents a significant metabolic burden for the yeast cells, which results in oxidative stress and ultimately affects the protein production capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The mitochondrial staining method was described in a previous publication (49). Briefly, the cells were cultivated in SD-2xSCAA medium using tube fermentation and harvested when the OD 600 was Ϸ1.…”
Section: Methodsmentioning
confidence: 99%
“…The mitochondrial staining method was described in a previous publication (49). Briefly, the cells were cultivated in SD-2xSCAA medium using tube fermentation and harvested when the OD 600 was Ϸ1.…”
Section: Methodsmentioning
confidence: 99%
“…Normally, heme biosynthesis is under tight control of the transcription factor Rox1p, which prevents cellular heme accumulation via repression of HEM13. Rox1p itself is controlled by Hap1p activity, which in turn is activated by high heme levels (Martínez et al 2016). Interestingly, overexpression of HAP1 gene has recently been shown to have a profound effect on growth and to some extent protein expression (Martínez et al 2015) putatively by induction of oxidative stress response and expression of enzymes involved in respiration.…”
Section: Verification Of Phenotypes Using Defined Deletions Of Targetmentioning
confidence: 99%
“…It was shown that free radicals and reactive species are linked to endoplasmic reticulum (ER) stress and the unfolded protein responses (UPR) in different cells, which activate a set of oxidative stress response genes, mainly those associated with protein folding. These responses mitigate the negative effects of ROS accumulation and hence increase the production capacity 20 . The plasma jet produces a variety of ions and free radicals in the gas phase.…”
Section: Discussionmentioning
confidence: 99%